Incentivizing Effort and Informing Investment: The Dual Role of Stock Prices - Banerjee, Snehal; Davis, Jesse; Gondhi, Naveen (Review of Financial Studies, 2026)
Abstract Stock prices aggregate investor information about investment opportunities and reflect managerial performance. These dual roles may be in tension: when prices are more informative about investment opportunities, they may be less effective at incentivizing managerial effort. This tradeoff has novel consequences. Lower information costs can lead to both more efficient investment but lower firm value. The principal may strictly prefer to delegate investment to a manager who has no informational advantage and makes ex-post inefficient choices. Investment in diversifying and (ex-ante) negative NPV projects mitigate agency problems. Finally, standard measures of price efficiency provide an incomplete picture of firm value.